Refrigerator temperature controller / Aznida Ramli and Afzan Zainal - Ramli, Aznida; Zainal, Afzan (2001)
All refrigerator are incorporated with a temperature controller which can be used to adjust its inside temperature. This device is usually complicated and cannot be repaired easily. Our project is designed to build a cheap and effective electronic temperature controller The temperature converted into voltage by means of zener 1C1 (LM 335) which holds its voltage at 2.73v at 0uC.When the temperature increases, the zener voltage increases linearly by 10mV/°C. An elaborate circuit is needed to disconnect the auxiliary winding inside the compressor in this project we used three les; LM335 (zener diode), CA3140 (op-amp) and 7812,12V(regulator).